Preventive Efficacy of Domestic Vaccines against a New Coronavirus Infection in the Immunization of Employees of Medical Organizations - I. V. Feldblum; T. M. Repin; M. Y. Devyatkov; V. V. Semerikov; M. A. Gileva; A. A. Kovtun; N. I. Markovich (Эпидемиология и вакцинопрофилактика)
Relevance. Evaluation of the preventive effectiveness of domestic vaccines in immunization of employees of medical organizations, in the context of the ongoing pandemic caused by the SARS-CoV-2 virus, remains important. The aim. To evaluate the preventive effectiveness of domestic vaccines in the immunization of employees of medical organizations. Materials and methods. The preventive efficacy of domestic vaccines was studied in an epidemiological, analytical, retrospective (historical), cohort, parallel study involving 1115 healthcare workers from various outpatient and policlinic organizations in the city of Perm. Results. The high preventive efficacy of COVID-19 vaccination of health care workers was established in the conditions of analytical cohort study (the incidence of the unvaccinated was 3.3 times higher than the incidence of vaccinated). Among the vaccinated, a milder course of the disease was observed. The GamCovidVac Spuntic V and Sputnik Light vaccines were characterized by the highest prophylactic efficacy for which was 76.1 and 78.2 respectively, against 54.53 with Covivac immunization and 50.7 with EpiVacCorona. Conclusions. Vaccination is an effective measure against COVID-19 and can be recommended in the context of ongoing pandemic.